Enhancing Electron Correlation at a 3D Ferromagnetic Surface (Adv. Mater. 3/2023). Issue 3 (19th January 2023) - Janas, David Maximilian; Droghetti, Andrea; Ponzoni, Stefano; Cojocariu, Iulia; Jugovac, Matteo; Feyer, Vitaliy; Radonjić, Miloš M.; Rungger, Ivan; Chioncel, Liviu; Zamborlini, Giovanni; Cinchetti, Mirko
Abstract : Electron Correlation In article number 2205698, David Maximilian Janas, Andrea Droghetti, Giovanni Zamborlini, and co‐workers use state‐of‐the art photoemission spectroscopy and theoretical methods to unravel the origin of enhanced electron correlation at the interface between iron and an oxygen adsorbate layer. Since the degree of correlation is controlled by interface charge transfer, it can be easily engineered by selecting different adsorbates. This strategy could allow the design of low‐dimensional materials in yet‐unexplored intermediate correlated regimes. Image credit: Mira Sophie Arndt.